2010
DOI: 10.1016/j.chemosphere.2009.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the water soluble fraction from “alpeorujo” by Coriolopsis rigida: The role of laccase in the process and its impact on Azospirillum brasiliense survival

Abstract: The objective of this work was to evaluate the ability of the white rot basidiomycete Coriolopsis rigida to detoxify the water soluble fraction from "alpeorujo" (WSFA), a solid by-product produced by the olive oil extraction industry and characterized by a high concentration of phenols which limits its use as fertilizer and/or amendment. C. rigida reduced the phenol content in the liquid media supplemented with WSFA at 10 and 20% (v/v) after 15d of incubation. The analysis of WSFA toxicity after fungal treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
0
23
1
11
Order By: Relevance
“…Larger the seed was, less sensitive was to the chemicals. Larger seed may correlate with their higher capability to neutralize the toxic chemicals, possibly via the various mechanisms of degrading the toxic chemicals [3,[15][16][17]. Although we did not observe a similar correlation in the studies with TCP, it could be due to the fact that TCP was much more toxic than phenol and so the differential tolerance of the seed could not be observed.…”
Section: Discussioncontrasting
confidence: 51%
“…Larger the seed was, less sensitive was to the chemicals. Larger seed may correlate with their higher capability to neutralize the toxic chemicals, possibly via the various mechanisms of degrading the toxic chemicals [3,[15][16][17]. Although we did not observe a similar correlation in the studies with TCP, it could be due to the fact that TCP was much more toxic than phenol and so the differential tolerance of the seed could not be observed.…”
Section: Discussioncontrasting
confidence: 51%
“…It is known that saprobe fungi possess extracellular laccase and peroxidase that can degrade phenolic compounds (Aranda et al 2006(Aranda et al , 2007Sampedro et al 2004;Saparrat et al 2010). Consistently, when plants were grown in the presence of ADOR bioremediated with P. chrsysogenum-10, the increase in phenolics in roots was appreciably reduced and only showed significant differences 4 days after treatment.…”
Section: Ador Effects On Morpho-physiological Parameters Of Tomato Plmentioning
confidence: 51%
“…The ability of saprobe fungi to bioremediate DOR is due to the presence of extracellular enzymes, namely laccase and peroxidase (Aranda et al 2006(Aranda et al , 2007Sampedro et al 2004). It has been demonstrated that a relationship exists between the production of laccase by the saprobe fungus Coriolopsis rigida and degradation of phenolic compounds in aqueous extracts of DOR (ADOR) (Aranda et al 2006(Aranda et al , 2007Saparrat et al 2010). In addition, previous studies show that the production of hydrolytic enzymes by the saprobe fungus Penicillium chrysogenum-10 leads to a decrease in ADOR phytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the resultant suspension was centrifuged at 5,000 g for 5 min and the pellet was dried in an oven at 40°C overnight. Dry mycelium was embedded in infrared grade KBr disk (2 mg 20 mg −1 ) and recorded in a Perkin-Elmer-Instruments spectrometer (scanning range: 400-4,000 cm −1 , resolution: 4 cm −1 , number of scans: 64), the data of which was processed by means of the software OMNIC (Thermo Nicolet, Madison, WI) according to Saparrat et al (2010). This experiment was performed once with three replicates.…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%